Guangzhou Green Trucks Pilot Project : Background Analysis Report - Clean Air Initiative for Asian Cities Center (Clean Air Initiative for Asian Cities Center and the World Bank, Washington, DC, 2013)
This document was devloped as it initiated a pilot project - dubbed Guangzhou Green Trucks Pilot Project in support of Guangzhou's efforts to improve air quality in preparation for the 2010 Asian Games. The goal of this project was to develop a proof of concept for a truck program in Guangdong Province, and possibly China, that aims to: Enhance the fuel economy of the truck fleet, Reduce black carbon and other air pollutants from trucks and consequently obtain GHG emission savings.The project was implemented by the Clean Air Initiative for Asian Cities Center (CAI-Asia Center), in cooperation with Cascade Sierra Solutions, US EPA and World Bank, and with support from Guangzhou Environmental Protection Bureau (GEPB), Guangzhou Transport Committee (GTC), and Guangzhou Project Management Office (PMO) for the World Bank.The pilot project aims to contribute to addressing three problems related to trucks in Guangzhou and the wider Guangdong province simultaneously: (a) fuel costs and security; (b) air pollution and associated health impacts, and (c) greenhouse gas emissions and climate change. The scope of the pilot was limited to Guangdong Province, focusing on diesel trucks accessing or passing through the city of Guangzhou and surrounding cities, like Shenzhen. Aside from GHG emissions, the scope includes black carbon and other air pollutants from trucks because of their potential interacting effects and contribution to climate change, and because air pollution is an important local concern. The pilot project consisted of the following components, each with its own output: Background analysis, Survey of Guangzhou truck sector, Driver training course for fuel efficiency of trucks and a Technology pilot.